(untitled) (Zaporizhzhia Historical Review, 2021)
The main problems of the Teaching History Science, which Ukraine came across because of getting the independence, are regarded. Also the author researches the evolution process in the understanding the phenomenon ìnationî and various approaches to the studying of the ìnationî at school, in what way the education has influenced the Ukrainian reality as well. Should be noted that since the nineties of the 20th century the transformation from ìbadî or ìethnicî nationalism, which is typical for the Eastern Europe, to ìgoodî or ìcivilî nationalism of the Western Europe has taken place in the Ukrainian textbooks. The conclusion is that the studying of nation-making problem caused the significant changes in the social realization as for the national identity for the nation.